Some unresolved complexities in matters involving paternity: a South African Perspective - Albertus, Latiefa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
A controversial aspect regarding paternity in South African law is whether or not South African Courts are empowered to compel an adult or a minor to submit to DNA/blood tests. The High Courts were not unanimous in this regard, and thus the issue required clarification by the Supreme Court of Appeal (SCA). An opportunity presented itself for the SCA to not only address the issue of the use of DNA/blood tests in paternity matters, but several other issues surrounding paternity. The judgment by the SCA has, it is argued, unfortunately resulted in more questions than answers.